Penerapan Model Stad Berbantuan Media Ular Tangga terhadap Motivasi Belajar Siswa pada Materi Keliling dan Luas Bangun Datar Kelas V - Kristi, Tabita; Humairo, Yumna; Pratiwi, Eva; Firgiawan, Diva; Nawang, Dewi (Papanda Journal of Mathematics and Science Research, 2024)
This research aims to increase the mathematics learning motivation of class V students at SDN Mangkang Wetan 03, especially in understanding geometric concepts related to calculating the perimeter and area of ​​flat shapes. Initial observations show how difficult it is for students to understand the material and the lack of variation in the use of media and learning models. To overcome this problem, researchers applied the STAD type Cooperative Learning learning model with the help of the media "Mathematical Snakes and Ladders." This research uses a qualitative descriptive method with a focus on a comprehensive description of student learning motivation. The data in this research was collected through interviews, observation and documentation at SDN Mangkang Wetan 03, Semarang City. A saturated sampling technique was used, with all 23 fifth grade students as the sample. The results of the research show that the combination of the STAD learning model and mathematics snakes and ladders media succeeded in increasing students' excitement in learning mathematics. Students' active participation and cooperation in the STAD model, together with their enthusiasm in responding to the material through the medium of mathematical snakes and ladders, makes a positive contribution to students' understanding of the concepts of perimeter and area of ​​flat shapes.